Novel N, P-containing oil-soluble ionic liquids with excellent tribological and anti-corrosion performance. (April 2019) - Yu, Qiangliang; Zhang, Chaoyang; Dong, Rui; Shi, Yijun; Wang, Yurong; Bai, Yanyan; Zhang, Jiaying; Cai, Meirong; Zhou, Feng
Abstract: Two oil-soluble ionic liquids N, N-trimethyl-N-hexadecyl ammonium bis(2-ethylhexyl) phosphate (NP-16))and 1, 2-bis- N, N -dimethyl- N -cetylammonium bis (2-ethylhexyl) phosphate (NP-16-2-16) have been synthesized and investigated as a potential friction reduction and anti-wear lubricant additive with anti-corrosion properties. The results indicate that the addition of 1.0 wt % NP-16 into PAO10 can significantly reduce friction coefficient and improve its anti-wear performance under RT and 100 °C. The performance is obviously better than that of traditional additives ZDDP and tricresyl phosphate. PAO10 + 1.0 wt % NP-16 even outperformed the PAO10 with about 40% lower friction and 2 orders of magnitude less wear. The analysis results of SEM, EDS and XPS show that an FePO4 or nitrogen-containing tribofilm is formed on the friction interface when NP-16 and NP-16-2-16 are selected as additives, which play a key role in reducing friction and wear. Highlights: Two novel oil-soluble ILs is composed of same anion but different cations, i.e. one with single cation (NP-16) and the other with double cation (NP-16-2-16). The 1 wt % NP-16 into PAO10 can significantly reduce COF and improve its anti-wear performance under RT and 100 °C. The comparison study showed that the NP-16 and NP-16-2-16 exhibit higher PB and anti-corrosion properties. The facile preparation, high thermal stability, extremely eminent solubility and outstanding tribological properties of NP-16 make it a promising high-performance additive for PAO.